2011
DOI: 10.4489/kjm.2010.39.3.223
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Endophytic Fungi Isolated from the Rootlet of Pinus densiflora Colonized by Tricholoma matsutake

Abstract: : Endophytic fungi were isolated from the Pinus densiflora rootlet colonized by ectomycorrhizal fungus Tricholoma matsutake. Eighteen species of endophytic fungi were identified by analyzing rDNA-ITS sequence. As the result of the rDNA-ITS analysis, ascomycota of 15 species and Mucoromycotina of 3 species were isolated. Of all the endophytic fungi isolated, Penicillium sp. was confirmed as the highest frequency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 9 publications
3
8
0
Order By: Relevance
“…In this study, non- Trichoderma species were also isolated ( S1 Table ) and had similar species composition with previous studies conducting from PM fairy rings [ 16 , 17 , 22 ]. As Penicillium was most abundant species in You et al [ 22 ], the number of Penicillium species and strains was highest among non- Trichoderma species ( S1 Table ). In addition, Mortierella and Umbelopsis have been abundantly detected previously from PM fairy ring [ 16 , 20 , 22 ], and we isolated three Mortierella and two Umbelopsis species.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…In this study, non- Trichoderma species were also isolated ( S1 Table ) and had similar species composition with previous studies conducting from PM fairy rings [ 16 , 17 , 22 ]. As Penicillium was most abundant species in You et al [ 22 ], the number of Penicillium species and strains was highest among non- Trichoderma species ( S1 Table ). In addition, Mortierella and Umbelopsis have been abundantly detected previously from PM fairy ring [ 16 , 20 , 22 ], and we isolated three Mortierella and two Umbelopsis species.…”
Section: Discussionsupporting
confidence: 77%
“…Previous study showed that various saprotrophic fungi co-existed with PM colonized rootlets of Pinus densiflora , while Trichoderma was not found [ 22 ], likely due to difference of sampling strategy; lateral roots were used in this study, while rootlets were used in You et al [ 22 ]. In this study, non- Trichoderma species were also isolated ( S1 Table ) and had similar species composition with previous studies conducting from PM fairy rings [ 16 , 17 , 22 ]. As Penicillium was most abundant species in You et al [ 22 ], the number of Penicillium species and strains was highest among non- Trichoderma species ( S1 Table ).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Molds could be separated into two groups according to suppression pattern: a generally suppressed group (mGroup 1) and a specifically influenced group (mGroup 2) ( Fig 4 ). The generally suppressed group was composed of Absidia , Mucor , Penicillium , and Sarocladium , which were abundant in environments associated with PM, including the fruiting body [ 16 ], ectomycorrhiza [ 61 ], and soil [ 62 ]. Thus, it is possible that frequently detected molds may be more likely to be suppressed by abundant fruiting body bacteria ( Fig 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Umbelopsis was frequently detected from the fruiting body and the fairy ring of T . matsutake [13, 69, 70]. Because Umbelopsis species formerly belonged to Mortierella , Umbelopsis isolated from the fairy ring was identified as Mortierella [71].…”
Section: Discussionmentioning
confidence: 99%